Most frequent pediatric diseases in an international airport in Mexico: Enfermedades pediátricas que se encuentran con mayor frecuencia en un aeropuerto Internacional de México - Figueroa Uribe, Augusto Flavio (2021)
The frequency in which people travel internationally increases the potential for transmission of infectious diseases. The main causes of disease in children and adolescents vary according to the age group. Prevention is the most important action to take in public health, as it cannot be carried out if the diseases are not detected in a timely manner. The purpose of this study was to identify the most frequent pediatric diseases in the Emergency Medical Service of an international airport in Mexico. The study was observational, descriptive, retrospective and cross-sectional. It is concluded that diseases of digestive (presumed infectious gastroenteritis) and respiratory origin (pharyngitis) were the most frequent. This information can be used not only as a basis for decisions regarding public health, but also for the selection of equipment and supplies to be used in the medical service of an airport (pre-hospital care), in addition to the type of training required by the medical personnel.